Impact of Poverty Reduction Programs on Healthcare Access in Remote Ar-eas: Fostering Community Development for Sustainable Health - Amri, Siskawati; Sihotang , Jonhariono (Institute for Law and Economics Studies, 2023)
This research investigates the impact of poverty reduction programs on healthcare access in remote areas, aiming to discern their effectiveness in addressing healthcare disparities. Employing a mixed-method approach, the study combines quantitative surveys, qualitative interviews, and focus group discussions to gather comprehensive data. The research reveals promising outcomes, demonstrating a significant increase in healthcare utilization among communities benefiting from poverty reduction initiatives. Improvements in healthcare infrastructure, positive health outcomes, and economic empowerment are evident, indicating the success of these programs in enhancing healthcare access. However, limitations including geographical constraints, potential biases, and sample representativeness are acknowledged. While acknowledging these constraints, the findings emphasize the significance of continued support for poverty reduction programs, policy development, and community involvement to sustain and expand the positive impact on healthcare access in remote areas. This research offers vital insights, contributing to academic knowledge, policy development, and practice, supporting the global agenda of sustainable development goals and advocating for more inclusive and equitable healthcare access in marginalized regions